State-of-the-art review and future research directions for FRP-to-masonry bond research: Test methods and techniques for extraction of bond-slip behaviour. (20th September 2018) - Vaculik, J.; Visintin, P.; Burton, N.G.; Griffith, M.C.; Seracino, R.
Highlights: Collates the results of 1583 masonry pull-test results obtained from 56 studies. Inconsistency in test arrangements, instrumentation methods, and data processing identified. Lack of reported properties hinders the development of a bond model. Abstract: The effectiveness of FRP retrofits is heavily reliant on the shear bond that can be developed between the FRP and masonry substrate, which has been the focus of experimental research for almost two decades. This paper collates and critically reviews previous experimental work on the shear bond between FRP composites and masonry substrates, identifying 1583 individual pull-tests across 56 published studies. Whilst the pool of existing data is significant in terms of number of tests, it encompasses a rather narrow range of substrate material, FRP material and retrofit configuration. Most notably, the majority of tests have been undertaken on clay brick substrates, carbon FRPs and externally-bonded retrofits. By contrast, testing of natural stone substrates and near-surface-mounted retrofits has been limited. Significantly, the review identifies considerable inconsistency in the test arrangements, instrumentation methods, and data processing techniques for extracting local bond-slip properties, which has undoubtedly hindered the development of a unified bond model and codifiable design rules. Methods of extracting bond-slip behaviour from test data are critically reviewed, and importantly it is shown through numerical examples that without adequate instrumentation it is not possible to reliably extract this behaviour from standard pull-tests. Finally, suggestions for adequate instrumentation and a framework for undertaking bond-slip behaviour extraction through inverse analysis are presented. Significantly, the experimental database compiled as part of this work-thought to be the largest of its kind to date—is made openly available as an accompanying Data in Brief article with the intent that it will facilitate development of bond-strength models for FRP bonded to masonry.